2022
DOI: 10.1161/str.53.suppl_1.1
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1: Vagus Nerve Stimulation Paired With Rehabilitation For Upper Limb Motor Function After Ischaemic Stroke: Sub-group Analysis Of The Randomised, Blinded, Pivotal, Vns-Rehab Device Trial.

Abstract: Background: Vagus Nerve Stimulation (VNS) paired with rehabilitation improved upper extremity impairment and function in a recent pivotal, randomised, blinded, sham-controlled trial. Here we report post-hoc sub-group analyses from the VNS Rehab trial. We aimed to determine whether treatment effects were consistent across subgroups. Methods: VNS Rehab included 108 participants with moderate to severe arm /hand weakness, at least nine months after ischaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, stroke is dichotomized according to sex and different underlying diseases or drugs may change the effects of VNS through neuroregulatory pathway activation ( 4 ). However, preclinical trials have demonstrated that age does not limit the use of VNS in stroke treatment ( 16 ); Dawson et al ( 53 ) have conducted further detailed subgroup analyses of their patients after their clinical trials in 2021 and found that differences among different subgroups, including age, sex, residence location, stroke severity, stroke duration, side of the palsy, and cortical involvement, did not affect patient outcomes. An exploratory study by David et al ( 54 ) examined various predictors in combination with two clinical trials and led to the hypothesis that VNS provides additional benefits for patients with more severe upper extremity disability at baseline and unfavorable imaging outcomes (e.g., higher cerebrospinal fluid volume), with no other findings inconsistent with previous speculations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stroke is dichotomized according to sex and different underlying diseases or drugs may change the effects of VNS through neuroregulatory pathway activation ( 4 ). However, preclinical trials have demonstrated that age does not limit the use of VNS in stroke treatment ( 16 ); Dawson et al ( 53 ) have conducted further detailed subgroup analyses of their patients after their clinical trials in 2021 and found that differences among different subgroups, including age, sex, residence location, stroke severity, stroke duration, side of the palsy, and cortical involvement, did not affect patient outcomes. An exploratory study by David et al ( 54 ) examined various predictors in combination with two clinical trials and led to the hypothesis that VNS provides additional benefits for patients with more severe upper extremity disability at baseline and unfavorable imaging outcomes (e.g., higher cerebrospinal fluid volume), with no other findings inconsistent with previous speculations.…”
Section: Discussionmentioning
confidence: 99%